Assessing reflective models in marketing research: A comparison between pls and plsc estimates - Cheah, J.-H. (Universiti Malaysia Sarawak, 2018)
The present study aims at contributing to the growing discourse on analytical methods in marketing research by highlighting the use of Consistent Partial Least Squares (PLSc) estimation to assess reflective models used in marketing literature. Specifically, it demonstrates the significance of using PLSc and compares it with the traditional PLS. The results show that PLSc is more robust than traditional PLS in estimating convergent validity and path coefficients, and yields better power â coefficient of determination (R2) and effect size (f2). It is also found that PLSc generates better holdout results than traditional PLS. This study complements and extends prior research on PLSc, and subsequently serves as a resource for marketing researchers who use variance-based approach in their research. Implications, guidelines and future research directions are discussed. Â© 2018, Universiti Malaysia Sarawak. All Rights Reserved.